(untitled) (Journal of Student Affairs in Africa, 2025)
The peer mentor programme at the Vaal University of Technology has changed from being incentivised to a volunteer programme. Volunteering is considered a service to others without substantial remuneration. We assumed mentors could benefit from volunteering by developing their skills and social networks, enhancing their employability profile, and experiencing life satisfaction in serving others. However, in practice, structural changes in the programme contributed to low morale among mentors and a higher dropout. Hence, measures were taken to facilitate a more positive volunteer experience. Therefore, the study aimed to deepen understanding of student motives for volunteering and how to encourage sustained volunteering efforts. The study utilised two data sources to uncover volunteer peer mentors’ motivations. The multi-theoretical analytical framework allowed for insights not otherwise accessible. Most participants held volunteering a worthwhile pursuit. They reported enhancement or esteem as their strongest motivator for volunteering, followed by value expression and increased knowledge and skills. Healthy ego functioning or identity manifested as central to a coherent volunteer peer mentor experience. Ultimately, understanding and meeting volunteer mentors’ motivational needs leads to enhanced efforts and benefits not just for them as volunteers but also for first-year students and the university itself.